IMPROVEMENT OF TECHNICAL AND TACTICAL SKILLS AND COORDINATION ABILITIES OF JUDOKAS AGED 16-17 (Physical Culture and Sport: Scientific Perspective, 2023)
The article investigates the dynamics of technical and tactical skills and coordination abilities of judokas of 16-17 years old of middle weight categories under the influence of the proposed complexes of tasks and exercises. The proposed complexes for the improvement of technical and tactical skills consisted of tasks for the performance of technical actions in a stance, including the fight with different opponents and a complex of technical actions in the floor position, which consisted of situational exercises and the fight with opponents of different weight categories. The following means for improving coordination abilities are recommended: exercises with the use of non-standard starting, intermediate or final positions; reducing the space in which wrestlers move; performing well-mastered movements in non-standard conditions; exercises with maintaining balance on fitballs from different starting positions. The obtained results show that during the pedagogical experiment the sportsmen of the control group who trained according to the program of the Children and Youth Sports School changed the tactics of a competitive fight and began to make fewer attempts to realize technical actions, but the quality of points decreased. Sportsmen of the experimental group who trained on the offered complexes also began to make less attempts for realization of technical actions, but quality of points at the same time on the contrary increased, also, the volume and efficiency of technical actions increased. Comparing the results of testing the coordination abilities of judokas of the control and experimental groups, statistically significant changes in all tests are observed (p
Keywords: judo; technical and tactical skills; coordination abilities; tasks; exercises